2008
DOI: 10.1093/cvr/cvn229
|View full text |Cite
|
Sign up to set email alerts
|

Late exercise training improves non-uniformity of transmural myocardial function in rats with ischaemic heart failure

Abstract: This study shows that exercise performed at a late stage after MI restored a transmural non-uniformity of myocardium lost during HF. Recoveries of Ca(2+) homeostasis and myofilament function of cardiomyocytes contribute to this beneficial effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 41 publications
8
52
2
Order By: Relevance
“…This contrasts with a study in mouse ventricular cardiomyocytes that described transmural differences in action potential waveforms, SR Ca 2+ release, and Na + -Ca 2+ exchanger function that underlie differences in [Ca 2+ ] i and EC coupling across the left ventricular free wall [39]. We also observed a similar gradient of EC coupling from epicardium to endocardium in rats [3]. These data indicate that the regional contractile heterogeneity is not limited to the excitation and Ca 2+ release steps and that heterogeneous properties and/or regulation of the contractile machinery should be considered as well.…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This contrasts with a study in mouse ventricular cardiomyocytes that described transmural differences in action potential waveforms, SR Ca 2+ release, and Na + -Ca 2+ exchanger function that underlie differences in [Ca 2+ ] i and EC coupling across the left ventricular free wall [39]. We also observed a similar gradient of EC coupling from epicardium to endocardium in rats [3]. These data indicate that the regional contractile heterogeneity is not limited to the excitation and Ca 2+ release steps and that heterogeneous properties and/or regulation of the contractile machinery should be considered as well.…”
Section: Introductioncontrasting
confidence: 99%
“…The impact of muscle length in this sensitization was however not investigated. Nevertheless, we have recently demonstrated that stretch can induce phosphorylation of MLC-2 which contributes to LDA [2,3,25]. The role of TnI phosphorylation in LDA regulation has also been extensively explored (see for review [33]).…”
Section: Lda Molecular Basismentioning
confidence: 99%
See 3 more Smart Citations